Mathematical creative thinking ability based on students’ characteristics of thinking style through selective problem solving learning model with ethnomatematics nuanced - Zaenuri, Zaenuri; Nastiti, Putri Ambar; Suhito, Suhito (Department of Mathematics, Universitas Negeri Semarang, 2019)
This study aimed to determine the effectiveness of the Selective Problem Solving (SPS) model with ethnomatematics nuances on students' mathematical creative thinking abilities and describe mathematical creative thinking abilities based on students' characteristics of thinking style by applying Selective Problem Solving model with ethnomatematics nuances. The study population were VII grade students one of Junior High School in Magelang in the academic year of 2017/2018. The study sample were students of class VII B with Selective Problem Solving learning model with ethnomatematics nuances and students of class VII G with Problem Based Learning (PBL) model. They were chosen through cluster random sampling technique. Quantitative data were analyzed using normality, homogeneity, proportion test, independent sample t-test, and paired sample t-test. Qualitative data were analyzed using data validation, data transcript, reduction, data presentation, and conclusions. The results showed that students 'mathematical creative thinking ability in Selective Problem Solving learning model with ethnomatematics nuances has not yet reached classical completeness, students' mathematical creative thinking ability in Selective Problem Solving learning model with ethnomatematics nuances was better than students' mathematical creative thinking ability in Problem Based Learning (PBL) model, there were differences of students interest on local culture before and after learning in Selective Problem Solving learning model with ethnomatematics nuances, sequential concrete thinking type, namely subjects fulfilled the indicator of fluency and the indicator of flexibility and were enough in fulfilling the indicator of novelty, sequential abstract thinking type showed that subjects fulfilled the indicator of fluency and less fulfilled the indicator of flexibility and novelty, random abstract thinking type revealed that subjects less fulfilled the indicator of fluency and not fulfill the indicator of flexibility and novelty, and random concrete thinking type showed that subjects less fulfilled the indicator of fluency and flexibility and did not fulfill the indicator of novelty.